Fabrication of three dimensional SiC@C hybrid for efficient direct dehydrogenation of ethylbenzene to styrene. (20th March 2022) - Wang, Jiashun; Wang, Linlin; Diao, Jiangyong; Xie, Xi; Lin, Guoming; Jia, Qing; Liu, Hongyang; Sui, Guoxin
Highlights: The 3D carbon decorated SiC hybrid (core-shell structure) is first prepared by a simple template method as a potential robust metal free ethylbenzene DDH catalyst. The SiC@C catalyst exhibits a large specific area (410.30 m 2 g −1 ) and high catalytic activity (11.58 mmol g −1 carbon h −1 ) in DDH of EB, nearly 4 times that of nanodiamond. The extraordinary catalytic performance is attributed to the abundant surface carbonyl groups on the carbon layers. The unique 3D core shell structure can inhibit the aggregation of SiC@C nanocrystals and is benefit for the heat and mass transfer during the dehydrogenation reaction. Abstract: Synthesis of hybrid carbon materials with core-shell structure and robust catalytic performance is of great research interest, and remains a great challenge in catalytic dehydrogenation of hydrocarbons reaction. In this paper, few-layer sp 2 carbon decorated SiC nanocrystals with core-shell structure (SiC@C) were fabricated through a dual-confined magnesiothermic method by employing glucose and SiO2 as precursors. The SiC@C nanocrystals were further crosslinked to be a three dimensional (3D) mesoporous hybrid by the in situ generated carbon as binders and exhibiting a 410.30 m 2 g −1 large surface area. The as-prepared SiC@C hybrid materials as metal-free catalysts were evaluated in the steam-free direct dehydrogenation of ethylbenzene to styrene. Benefiting from the abundant surface carbonyl groups on the graphite carbon layers, the optimized yield rate of styrene normalized by carbon mass was as high as 11.58 mmol g −1 carbon h −1, nearly 4 times that of nanodiamonds. Considering the low cost and excellent catalytic activity, the hybrid 3D SiC@C material may be a promising candidate for direct dehydrogenation of hydrocarbons.